1993
DOI: 10.3109/10408449309105012
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Chromium Carcinogenicity and Toxicity

Abstract: Chromium, like many transition metal elements, is essential to life at low concentrations yet toxic to many systems at higher concentrations. In addition to the overt symptoms of acute chromium toxicity, delayed manifestations of chromium exposure become apparent by subsequent increases in the incidence of various human cancers. Chromium is widely used in numerous industrial processes, and as a result is a contaminant of many environmental systems. Chromium, in its myriad chemical forms and oxidation states, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
257
0
6

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 502 publications
(273 citation statements)
references
References 236 publications
10
257
0
6
Order By: Relevance
“…Chromium exists in two major oxidation states: +3, which is an essential nutrient, and +6, which is highly toxic and carcinogenic (Cieslak-Golonka 1996). It has been proposed that Cr(VI) is toxic because it can penetrate cells, be reduced to Cr(III), and then generate reactive oxygen species, such as hydroxyl radical, that can cause DNA damage (Cohen et al 1993). The highest exposures to Cr(VI)-containing particulate matter likely occurs to workers during welding, chrome plating, spray painting, and chrome pigment productions (Cohen et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromium exists in two major oxidation states: +3, which is an essential nutrient, and +6, which is highly toxic and carcinogenic (Cieslak-Golonka 1996). It has been proposed that Cr(VI) is toxic because it can penetrate cells, be reduced to Cr(III), and then generate reactive oxygen species, such as hydroxyl radical, that can cause DNA damage (Cohen et al 1993). The highest exposures to Cr(VI)-containing particulate matter likely occurs to workers during welding, chrome plating, spray painting, and chrome pigment productions (Cohen et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…It has been proposed that Cr(VI) is toxic because it can penetrate cells, be reduced to Cr(III), and then generate reactive oxygen species, such as hydroxyl radical, that can cause DNA damage (Cohen et al 1993). The highest exposures to Cr(VI)-containing particulate matter likely occurs to workers during welding, chrome plating, spray painting, and chrome pigment productions (Cohen et al 1993). However, a study in Los Angeles showed that ambient fine particles can also contain significant amounts of chromium and that the amount of Cr (relative to the total mass of metals) is greater in the ultrafine particles than that in the fine particles (Hughes et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic exposure to As leads to skin disorders such as hyperkeratosis and, in many cases, carcinogenesis (12,13). Both As and Cr, a well-known skin sensitizer, have substantial effects on epidermal keratinocytes in vitro and in vivo; these metals have been shown to alter expression of numerous growth regulatory factors, to stimulate cell proliferation at low concentrations, and to inhibit the normal process of differentiation (11,(14)(15)(16)(17)(18)(19). They have not, however, been shown to be directly transforming in this cell type.…”
mentioning
confidence: 99%
“…However, hexavalent chromium is a known carcinogen, mutagen, cytotoxicant and strong oxidizing agent (Flores and Pérez, 1999;Stearns et al, 1995). The Cr(VI) can cross cellular membranes via surface anion transport systems (SO 4 2− and HPO 4 2− channels) and is biologically active (Cohen et al, 1983). Chromium is used in numerous industrial applications that are responsible for widespread pollution of soil and groundwater (Chardin et al, 2002).…”
Section: Introductionmentioning
confidence: 99%